Inteins in Microbial Genomes: Distribution, Mechanism, and Function - Maurice W. Southworth; Francine B. Perler (The Scientific World Journal)
Inteins are self-splicing protein elements (134 to 608 amino acids). Over 125 inteins have been cataloged in InBase, the on-line intein database (http://www.neb.com/neb/inteins.html), which includes the Intein Registry[1]. Inteins naturally present in pathogenic microbes represent novel, yet unexploited drug targets. Understanding the chemistry of the splicing reaction has allowed the manipulation of inteins, which are now used in many protein engineering applications[2].